A New Look at Instersubjectivity and Theology: A Retrieval of Filipino Loob-Kapwa Relationality In Dialogue with Gabriel Marcel and Ludwig Binswanger - Rebustillo, Rowan (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2017)
Although Marcel and Binswanger are contemporaries both in terms of historical period and intellectual pursuit, it is curious that they are never discussed together. Hence, this essay will attempt to explore some areas of convergences and divergences between these two intersubjective thinkers who are considered to be indispensable interlocutors in the I-thou discourse. In this article, as another attempt to take the discourse on intersubjectivity a little bit further, Marcel and Binswanger are placed in dialogue with the Filipino concept of loob-kapwa, which the author believes provides a hospitable home, when seen against the background of Nicolescu’s “Included Middle”, for the intersubjective relation that they are proposing. The author asserts that loob-kapwa tandem, without turning a blind eye towards its negative tendencies, is a viable answer to the “problem of crossing-over” that remained to be a philosophical baggage for both Marcel and Binswanger courtesy of their Modern upbringing, because the chasm, at least conceptually, is absent in the Filipino estimation of the loob-kapwa intersubjective bond.